Expression Profiling of Ribosomal Protein Gene Family in Dehydration Stress Responses and Characterization of Transgenic Rice Plants Overexpressing RPL23A for Water-Use Efficiency and Tolerance to Drought and Salt Stresses - Moin, Mazahar; Bakshi, Achala; Madhav, M. S.; Kirti, P. B. (Frontiers in Chemistry, 2017)
Our previous findings on the screening of a large-pool of activation tagged rice plants grown under limited water conditions revealed the activation of Ribosomal Protein Large (RPL) subunit genes, RPL6 and RPL23A in two mutants that exhibited high water-use efficiency (WUE) with the genes getting activated by the integrated 4x enhancers (Moin et al., 2016a). In continuation of these findings, we have comprehensively characterized the Ribosomal Protein (RP) gene family including both small (RPS) and large (RPL) subunits, which have been identified to be encoded by at least 70 representative genes; RP-genes exist as multiple expressed copies with high nucleotide and amino acid sequence similarity. The differential expression of all the representative genes in rice was performed under limited water and drought conditions at progressive time intervals in the present study. More than 50% of the RP genes were upregulated in both shoot and root tissues. Some of them exhibited an overlap in the upregulation under both the treatments indicating that they might have a common role in inducing tolerance under limited water and drought conditions. Among the genes that became significantly upregulated in both the tissues and under both the treatments are RPL6, 7, 23A, 24 and 31 and RPS4, 10 and 18a. To further validate the role of RP genes in WUE and inducing tolerance to other stresses, we have raised transgenic plants overexpressing RPL23A in rice. The high expression lines of RPL23A exhibited low Δ13C, increased quantum efficiency along with suitable growth and yield parameters with respect to negative control under the conditions of limited water availability. The constitutive expression of RPL23A was also associated with transcriptional upregulation of many other RPL and RPS genes. The seedlings of RPL23A high expression lines also showed a significant increase in fresh weight, root length, proline and chlorophyll contents under simulated drought and salt stresses. Taken together, our findings provide a secure basis for the RPL gene family expression as a potential resource for exploring abiotic stress tolerant properties in rice.